TINJAUAN HUKUM ISLAM TERHADAP PERAN NOTARIS DALAM PEMBUATAN AKTA JUAL BELI (Studi Kasus Di Kantor Notaris/PPAT Manahan - Nursania Dasopang (Journal Khafi : Journal Of Islamic Studies, 2023)
The role of the Notary-PPAT in the services sector is as an official authorized by the State to serve the community in the notarial sector. The notarial field itself includes making sale and purchase deeds, gift deeds, inheritance distribution, granting mortgage rights, as well as the deed of establishment and articles of association of a company, and other deeds. In the practice of community life, there are still several legal acts aimed at transferring land rights that are not made by and before a Notary-PPAT. A notary is a public official who has the authority to make authentic deeds and other authorities as intended in Law Number 30 of 2004 concerning the Position of Notaries. Meanwhile, PPAT is a public official who is given the authority to make authentic deeds regarding certain legal acts regarding land rights or ownership rights to apartment units (Article 1 number 1 PP Number 37 of 1998).